2016
DOI: 10.1002/stem.2497
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length Defines the Cardiomyocyte Differentiation Potency of Mouse Induced Pluripotent Stem Cells

Abstract: Induced pluripotent stem cells (iPSCs) can be differentiated in vitro and in vivo to all cardiovascular lineages and are therefore a promising cell source for cardiac regenerative therapy. However, iPSC lines do not all differentiate into cardiomyocytes (CMs) with the same efficiency. Here, we show that telomerase-competent iPSCs with relatively long telomeres and high expression of the shelterin-complex protein TRF1 (iPSC ) differentiate sooner and more efficiently into CMs than those with relatively short te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 71 publications
5
12
0
Order By: Relevance
“…In agreement, Zeng et al demonstrated that telomeres were elongated during in vitro expansion and were then stabilized through a telomerase-dependent mechanism [32]. Our 2D and 3D expansion and directed differentiation of the revived cells demonstrated stable expression of telomerase and telomere length, as several studies have reported a correlation between short telomeres and unstable directed differentiation in mouse and human pluripotent cells [33,34].…”
Section: Discussionsupporting
confidence: 90%
“…In agreement, Zeng et al demonstrated that telomeres were elongated during in vitro expansion and were then stabilized through a telomerase-dependent mechanism [32]. Our 2D and 3D expansion and directed differentiation of the revived cells demonstrated stable expression of telomerase and telomere length, as several studies have reported a correlation between short telomeres and unstable directed differentiation in mouse and human pluripotent cells [33,34].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Imaizumi et al [40] and López et al [41] both observed no chromosomal structural abnormalities in cryopreserved human induced pluripotent stem cells and adipose-derived stem cells, respectively. Recently, it was shown that the differentiation potency of induced pluripotent stem cells was correlated with their telomere length [42]. These findings, coupled with our experiment data, offer convincing evidence that our cPDLSC sheets could maintain similar differentiation capacity as fPDLSC sheets.…”
Section: Discussionsupporting
confidence: 85%
“…For example, Mosteiro and colleagues found that senescence promoted in vivo programming of murine iPSCs, although the relevance of telomere integrity in this process was not directly assessed (Mosteiro et al, 2018). In cardiomyocytes stimulated to undergo iPSC reprogramming, there was an inverse correlation between reprogramming potential and telomere length (Aguado et al, 2016). In primary human cells undergoing senescence, H3K27me3 loss is correlated with gene expression changes that may drive senescence, and depletion of EZH2 contributes to the Senescence-Associated Secretory Phenotype (SASP) (Ito et al, 2018;Shah et al, 2013).…”
Section: Discussionmentioning
confidence: 99%